A method for preparing electromechanical responsive skin-core conductive composite fiber
By constructing a leather-core conductive composite fiber with pure TPU fiber as the core layer and CB/SEBS conductive layer as the cortex, the problems of electromechanical response attenuation and nonlinearity of electrical signals in simulation applications of conductive polymer composite materials are solved, and more stable strain sensing performance is achieved, which is suitable for human wearable fields.
Patent Information
- Application Number
- CN202310699074.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-06-14
AI Technical Summary
Conductive polymer composites have problems with electromechanical response attenuation and nonlinearity of electrical signals during simulation applications, which limits their practical application value in the fields of human wearables and electronic skin.
Using the preparation method of electromechanical responsive leather-core conductive composite fiber, a leather-core conductive composite fiber based on spiral-collected pure TPU fibers is constructed by using pure TPU fibers as the core layer, using CB/SEBS conductive layer as the cortex, combined with dopamine surface modification technology.
It improves the linear range of the electrical signal provided by the sensing fiber, reduces the impact of viscoelastic mechanical behavior on the signal attenuation, and achieves more stable strain sensing performance, which is suitable for the wearable field of human body.
Smart Images

Figure CN116536796B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material manufacturing, and in particular to a method for preparing an electromechanical responsive sheath-core conductive composite fiber. Background Art
[0002] Conductive polymer composites are a popular sensing material currently used for stress and resistance signal conversion. They have the flexibility advantage that traditional metal strain sensors do not have, and are more suitable for applications such as wearables and electronic skin. Although a lot of progress has been made in the research of strain sensors based on this material, this material still has problems such as electromechanical response attenuation and electrical signal nonlinearity when used in simulation applications. There are fewer studies on these bottleneck issues, but it is these problems that limit the practical application value of conductive polymer composites.
[0003] In practical applications in the wearable field, the electromechanical response of conductive polymer composites will be affected by the viscoelastic mechanical properties of the polymer, making it difficult to provide highly linear and stable sensing signals within a large strain range. This is the key issue that determines whether conductive polymer composites can be used in practical applications.
[0004] When the conductive filler is evenly dispersed in the polymer matrix, the overall stiffness of the system will increase, so the flexibility and recoverability will also decrease. At the same time, the movement of the conductive network is also affected by the relaxation of the polymer chain segments. The strain and signal size no longer show a linear relationship. At this time, CPCs materials do not have a high practical value. However, most researchers still focus on how to widen the response range or improve the sensitivity of the material (GF value), ignoring the problem that when the material provides the maximum sensitivity, its internal conductive network has tended to fail. At this time, the GF value is distorted. Conor S. Boland cited the concept of working factor, using the maximum strain value when the signal remains linear as the criterion for judging the quality of CPCs material strain sensing performance, and explained that increasing the working factor to 1 (when the strain rate is above 100%, the electrical signal can still remain linear) should be the correct direction for the development of CPCs materials. Summary of the invention
[0005] Based on this, the present invention provides a method for preparing an electromechanically responsive skin-core conductive composite fiber, aiming to improve the linear range of the electrical signal provided by the sensing fiber and reduce the attenuation effect of viscoelastic mechanical behavior on the signal.
[0006] To achieve the above object, the present invention provides a method for preparing an electromechanical responsive sheath-core conductive composite fiber, which comprises the following steps:
[0007] S1. Dissolving polyurethane in N,N-dimethylformamide to form a spinning solution, using a wet spinning device to extrude the spinning solution into a water bath to form nascent fibers, and collecting the nascent fibers that have passed through the water bath on a hard collecting tube in a spiral shape, with no intersections between the fibers, and then drying and annealing to obtain pure TPU fibers collected on the hard collecting tube in a spiral shape;
[0008] S2, adding Tris to deionized water and stirring to dissolve, measuring the real-time pH value of the solution, and dropping hydrochloric acid into the solution until the pH value drops to 8.5 to obtain a Tris-HCl buffer solution; adding dopamine hydrochloride to a mixed solution prepared by Tris-HCl buffer solution and anhydrous ethanol to dissolve, to obtain a dopamine solution; immersing the pure TPU fiber along with the hard collecting tube in the dopamine solution, and stirring for 12 to 24 hours under aerobic conditions at room temperature and away from light, then taking out the hard collecting tube, and finally rinsing with deionized water and drying to perform surface modification on the pure TPU fiber to obtain a modified fiber;
[0009] S3. Add hydrogenated styrene-butadiene block copolymer into cyclohexane and stir until completely dissolved, then add carbon black and stir ultrasonically to prepare a uniformly dispersed CB / SEBS conductive solution; immerse the modified fiber through a hard receiving tube into the CB / SEBS conductive solution for 0.5 to 2 hours, remove the fiber from the plastic tube, and dry it to obtain a sheath-core conductive composite fiber with a CB / SEBS layer as a conductive sheath and a TPU fiber as a core.
[0010] As a further preferred technical solution of the present invention, in step S1, polyurethane is dissolved in N,N-dimethylformamide at a concentration of 180-220 mg / mL to form a spinning solution.
[0011] As a further preferred technical solution of the present invention, in step S1, the as-spun fibers are bundled in a spiral shape on a receiving tube and dried and annealed in a blast oven at 80-90°C.
[0012] As a further preferred technical solution of the present invention, the average diameter of the pure TPU fiber obtained in step S1 is 130-150 μm, the average diameter of the modified fiber after surface modification in step S2 is 210-230 μm, and the diameter of the skin-core conductive composite fiber obtained in step S3 is 245-260 μm.
[0013] As a further preferred technical solution of the present invention, in step S2, the concentration of dopamine hydrochloride is 2 mg / mL, the concentration of Tris-HCl buffer is 0.01 mol / L, and Tris-HCl buffer and anhydrous ethanol are mixed in a volume ratio of 1:1.
[0014] As a further preferred technical solution of the present invention, in step S2, the volume fraction of carbon black in the CB / SEBS conductive solution is 25-45%.
[0015] As a further preferred technical solution of the present invention, in step S2, multi-walled carbon nanotubes with a volume fraction of 1 to 15% are further added to the CB / SEBS conductive solution.
[0016] The preparation method of the electromechanical response core-skin conductive composite fiber of the present invention, in order to reduce the attenuation of the electromechanical response and improve the stability of the sensing performance of the conductive fiber, constructs a core-skin conductive composite fiber with an elastomer of pure TPU fiber as the core layer and a CB / SEBS conductive layer as the skin layer. The pure elastomer is surface modified by using a dopamine-buffered solution, and the conductive layer is then coated after the surface adhesion is improved, thereby ensuring a good interface relationship. The core layer structure of the pure TPU fiber gives the fiber a relatively linear stress-strain relationship within a small strain range, so the core-skin fiber also has a very wide linear response range (>100% strain). The maximum GF value of the core-skin fiber within this range is 2.92, the response time is 449ms, the signal has no shoulder peak phenomenon, and the static relaxation time is extended by 170.67% compared with the homogeneous fiber, and has excellent and stable strain sensing performance. The preparation of the present invention achieves the purpose of improving the stability of the sensing performance, that is, successfully constructing a core-skin conductive composite fiber with more stable strain sensing performance and slow signal attenuation, which has great application potential in the field of human wearables. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0018] Figure 1 (a) Surface morphology SEM images of pure TPU fiber prepared in Comparative Example 1 at different magnifications.
[0019] Figure 2 (a) pure TPU fiber, (b) modified fiber, (c) SCCB fiber prepared in Example 1 35 SEM images of the surface morphology of the sheath-core fibers at different magnifications.
[0020] Figure 3 This is the XPS spectrum of the pure TPU fiber prepared in Example 1 before and after modification.
[0021] Figure 4 This is the curve of the conductivity of the CB / TPU homogeneous conductive composite fiber prepared in Comparative Example 2 as a function of the volume fraction of carbon black.
[0022] Figure 5 This is a curve showing the change in electrical conductivity of the CB-SEBS / TPU sheath-core conductive composite fiber prepared in Example 1 as a function of the volume fraction of carbon black.
[0023] Figure 6 This is the stress-strain curve of the CB-SEBS / TPU sheath-core conductive composite fiber prepared in Example 1.
[0024] Figure 7 This is the stress-strain curve of the CB-SEBS / TPU sheath-core conductive composite fiber prepared in Example 1 within the 100% strain range.
[0025] Figure 8 This is a curve diagram of the change of ΔR / R0 of the CB-SEBS / TPU sheath-core conductive composite fiber prepared in Example 1 with increasing strain.
[0026] Fig. 9 This is a curve diagram showing the change of ΔR / R0 value of the sheath-core fiber prepared in Example 1 as the strain increases by 80.0%.
[0027] Fig.10 For SCCB 35 Response behaviors of the sheath-core fibers under (a) small strains (0.5%, 1.0%, 2.0%, 3.0%) and (b) large strains (10%, 20%, 40%, 60%).
[0028] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0029] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0030] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0031] Comparative Example 1
[0032] Preparation of pure TPU fiber:
[0033] At room temperature, 6.0 g of dried polyurethane (TPU) particles were added to 30 mL of DMF solution and placed on a magnetic stirrer for 14 h to completely dissolve the TPU, thereby preparing a 200 mg / mL TPU / DMF spinning solution. Using a wet spinning method, the spinning solution was squeezed into a water bath at a speed of 0.08 mL / min from a 23G (hole inner diameter 0.34 mm) needle, collected in a traditional way, and placed in an 80°C blast oven for fiber annealing, and taken out after 10 minutes.
[0034] Comparative Example 2
[0035] A TPU / DMF solution with a concentration of 200 mg / mL was prepared and used as the spinning matrix stock solution. A certain mass of carbon black (CB) conductive filler was added to 5 mL of DMF solvent and ultrasonically dispersed for 2 hours to evenly disperse the conductive filler. 5 mL of TPU / DMF solution with a concentration of 200 mg / mL was added to the CB / DMF dispersion. The mixed solution was placed on a magnetic stirrer and stirred for 3.5 hours, and then ultrasonically dispersed for 0.5 hours to ensure the dispersibility of the conductive filler in the polymer solution. Then, the same wet spinning process as in Comparative Example 1 was used to obtain CB / TPU homogeneous conductive composite fibers. The homogeneous conductive composite fibers are named and distinguished according to the concentration of CB, such as: CB 12 , is a homogeneous conductive composite fiber with a CB volume fraction of 12%. In Comparative Example 2, different CB / TPU homogeneous conductive composite fibers were prepared by selecting CB volume fractions of 12%, 13%, 14% and 15%.
[0036] Example 1
[0037] (1) Preparation of pure TPU fiber:
[0038] First, polyurethane (TPU) was dissolved in N,N-dimethylformamide (DMF) to prepare a TPU / DMF solution with a concentration of 200 mg / mL as a spinning solution. Using the wet spinning method, the spinning solution was squeezed into the water bath at a speed of 0.08 mL / min from a 23G (hole inner diameter 0.34 mm) needle. The nascent fibers that had passed through the water bath were bundled in a spiral shape on a hard plastic hollow tube as a receiving tube. There were no intersections between the fibers to prevent the fibers from bonding to each other when they were not fully formed. Finally, the hard plastic tube bundled with pure TPU fibers was placed in a blast oven at 80°C, the residual solvent inside was evaporated and annealed, and the plastic tube was taken out after 10 minutes to obtain pure TPU fibers.
[0039] (2) Surface modification of pure TPU fiber:
[0040] A certain amount of Tris was added to deionized water and stirred. After the particles were dissolved, the real-time pH value of the solution was measured, and hydrochloric acid was added to the solution until the pH value dropped to 8.5 to obtain a Tris-HCl buffer solution with a concentration of 0.01 mol / L. Dopamine hydrochloride (concentration of 2 mg / mL) was added to a mixed solution of Tris-HCl buffer and anhydrous ethanol (volume ratio of 1:1) to dissolve to obtain a dopamine solution. The plastic tube bound with pure TPU fiber was vertically immersed in the dopamine solution, stirred for 24 hours under normal temperature, aerobic and light-proof conditions, and finally the plastic tube was taken out. In this process, dopamine self-polymerized to form a polydopamine layer growing on the fiber and the plastic tube wall, making the tube wall and fiber of the plastic tube turn dark brown. Finally, after rinsing the plastic tube with deionized water, it was dried in a fume hood for 2 hours to complete the surface modification and obtain the modified fiber.
[0041] (3) Preparation of skin-core composite fibers
[0042] Hydrogenated styrene-butadiene block copolymer (SEBS) was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.; carbon black (CB): average density of about 1.7 g / mL, purchased from Alfa Aesar (China) Chemical Co., Ltd. Take SEBS (5 mg / mL) and stir it in cyclohexane for 2 hours until it is completely dissolved, then add a certain mass of CB and stir it ultrasonically for 30 minutes to prepare a uniformly dispersed CB / SEBS conductive solution. After immersing the modified fiber (still tied to the plastic tube) in the CB / SEBS solution for 1 hour, the fiber is quickly removed from the plastic tube to prevent the fiber from bonding to the CB / SEBS coating coated on the plastic tube after the cyclohexane evaporates. At this time, the fiber is uniformly black, indicating that the CB / SEBS polymer has been evenly coated on the modified pure TPU fiber, forming a CB-SEBS / TPU skin-core conductive composite fiber with the CB / SEBS layer as the conductive skin and the pure TPU fiber as the core. Finally, the skin-core conductive composite fiber is named SCCB x , where SC represents the skin-core model and x represents the volume fraction of CB in the CB / SEBS conductive solution used, for example, SCCB 25 It is a sheath-core fiber with a CB volume fraction of 25% in the conductive coating.
[0043] The volume fraction of CB in the CB / SEBS conductive solution of the present invention is preferably 25-45%. The following skin-core conductive composite fibers prepared with CB volume fractions of 25%, 30%, 35%, 40%, and 45% are tested for conductive properties, mechanical properties, and strain sensing properties.
[0044] Scanning electron microscope test:
[0045] The pure TPU fiber of Comparative Example 1, the pure TPU fiber of Example 1, and the modified fiber SCCB 35 After the surface of the core-skin conductive composite fiber was treated with gold spraying, the fiber surface and cross-sectional morphology were characterized under an environmental scanning electron microscope (Quanta250). The obtained SEM images are shown in Figure 2 Figure 1 and Figure 2 As shown. Figure 1 (a) Pure TPU fiber and Figure 2 (a) The pure TPU fiber exhibits different surface morphology structures. Example 1 Since the TPU precursor was fixed on the hard tube before it was fully formed, and then it underwent a high-temperature annealing process, the solvent evaporated quickly, so the fiber surface was rough, with vertical ridges and a porous structure. Through this preparation method, we can obtain TPU fibers with a rough surface, which is to facilitate the subsequent self-polymerization of dopamine on the fiber surface. Figure 2 (b) After the fiber has undergone surface modification with polydopamine, we can see that polydopamine grows on the fiber surface in the form of agglomerated particles, and the groove structure on the fiber surface tends to be flat. Figure 2 (c) shows the surface morphology of the core-skin fiber. It can be seen that the CB / SEBS coating is uniform on the surface of the modified fiber. This is because the polydopamine layer provides an effective interaction between the TPU precursor and the CB / SEBS coating. As the modification process occurs, the addition of the dopamine layer increases the average diameter of the fiber from 145.1μm to 228.2μm. After the conductive layer is coated, the final average diameter of the core-skin fiber is 239.1μm.
[0046] Dopamine surface modification test:
[0047] X-ray photoelectron spectroscopy (XPS) (Escalab250Xi) was used to detect the element types and valence states in the pure TPU fiber and the modified fiber in Example 1, respectively, to analyze the effect of dopamine modification on the types of functional groups on the surface of the original fiber. The chemical formula of dopamine is C8H 11 NO2, which contains catechol and amino functional groups, has a similar functional group structure to DOPA (3,4-dihydroxyphenylalanine) with strong adhesion. Under light-proof aerobic conditions, dopamine can self-polymerize in a buffer solution with a pH of 8.5, and its color changes from colorless to brown and finally to black. The change in the color of the dopamine solution before and after self-polymerization is derived from pH-induced oxidation, which triggers the self-polymerization of dopamine. When pure TPU fiber is immersed in a dopamine solution, dopamine spontaneously deposits on the surface of the immersed material, so the color of the fiber also changes from white to black.
[0048] like Figure 3 , XPS elemental analysis was performed on the fiber surface composition before and after modification in Example 1, and it can be seen that the characteristic peaks of O1s, N1s and C1s are displayed at 532.5eV, 397.5eV and 285eV, respectively. By measuring the intensity of the peak, the content of each element on the surface of the sample under test is quantitatively analyzed. It is calculated that after the dopamine modification process, the signal ratio of the nitrogen and carbon elements is increased from 0.044 to 0.059, which is closer to the theoretical value of the nitrogen-carbon ratio of dopamine of 0.125. The modified fiber surface has a good affinity with the CB / SEBS coating, and the conductive coating can be evenly coated on the TPU fiber. After further comparative tests, it was found that if the TPU fiber is not subjected to the modification step, the CB / SEBS layer is directly coated on the TPU precursor. It is found that the bonding force between CB / SEBS and TPU is poor, the coating on the fiber surface is not uniform, and the fiber cannot show good conductive properties.
[0049] Conductivity test:
[0050] For conductive polymer composite materials, the filling of conductive fillers can realize the transformation of materials from insulators to conductors. According to the classical percolation theory, the conductivity of conductive composite fibers depends on the concentration of conductive fillers. When the concentration of conductive fillers is higher than a critical concentration, that is, the conductive percolation threshold, a relatively complete conductive network is formed inside the system, and the conductivity increases sharply. Figure 4 The conductivity of the CB / TPU homogeneous conductive composite fiber prepared in Comparative Example 2 varies with the volume fraction of carbon black. c ) t Fitting calculations show that the conductive percolation thresholds of CB / TPU conductive composite fibers are 11.90% and the fitting degrees are 0.9983. c )-logσ were linearly fitted and the fitting degrees were 0.9984.
[0051] like Figure 5 The conductivity of the CB-SEBS / TPU sheath-core conductive composite fiber prepared in Example 1 varies with the volume fraction of carbon black. Using the percolation model equation σ=σ0(pp c ) t The conductivity percolation thresholds of the core-skin fibers were calculated to be 24.20% and the fitting degree was 0.954. c)-logσ was linearly fitted and the fitting degree was 0.963. It can be found that the percolation threshold of the core-skin fiber is not superior to that of the CB / TPU homogeneous conductive composite fiber, but the cortex of the core-skin fiber occupies a smaller fiber volume. Compared with directly blending the conductive filler into the TPU matrix, the amount of conductive filler required for the core-skin fiber is much lower, which has the advantage of reducing the fiber preparation cost.
[0052] Mechanical properties test:
[0053] like Figure 6 This is the stress-strain curve of the CB-SEBS / TPU sheath-core conductive composite fiber during uniaxial stretching. Similarly, the basic mechanical properties of the sheath-core conductive fiber were studied with the fiber electrode resistance reaching 100MΩ as the end point. Tensile test parameters: initial sample length is 10.0mm, and the stretching rate is 20mm / min. As the volume fraction of carbon black in the cortex increases, the maximum stress value of the fiber when the resistance reaches 100MΩ shows a pattern of first increasing and then decreasing. SCCB 30 The maximum stress value of is the highest among all types of sheath-core fibers, which is 26.53MPa. Since the sheath and core layers of the fiber do not break at the same time during the stretching process, when part of the sheath breaks, the stress-strain curve will show some landslides. Since the mechanical properties of the sheath-core fiber are mainly controlled by the core layer of pure elastic body, the mechanical properties of several fibers are very similar, and within the strain range of 100%, the stress-strain curves of the fibers show good linearity. Figure 7 , with SCCB 25 Taking the fiber as an example, a linear fit was made to its stress-strain curve within the 100% strain range, and the goodness of fit reached 0.992, proving that the skin-core fiber has mechanical properties very close to those of a pure elastomer within the initial strain range.
[0054] Fiber sensing performance test:
[0055] The strain sensing performance of the core-skin conductive composite fiber comes from the response of the conductive network inside the cortex to external tensile deformation and the mechanical properties dominated by the core layer. As the cortex is deformed by strain stimulation, the conductive fillers become loose with each other, and the resistance of the fiber increases with the strain. However, the overall mechanical properties of the fiber are mainly controlled by the core layer, so the strain sensing performance of the core-skin fiber should be similar to the linear mechanical properties of pure elastomers in a low strain range. The strain sensing performance of CB-SEBS / TPU core-skin fibers coated with CB / SEBS solutions of different concentrations was tested, such as Figure 8 This is a curve diagram of the relative resistance of different CB-SEBS / TPU skin-core conductive composite fibers changing with increasing strain.
[0056] (1) Sensing response range of skin-core fiber
[0057] The maximum resistance of the fiber is 100MΩ. If the resistance exceeds this value, the fiber is considered to no longer have the ability to respond to electrical signals. That is, the strain range when the fiber resistance is 100MΩ is the maximum sensing response range. Table 1 records the response ranges of different skin-core fibers prepared in Example 1. It can be seen that as the volume fraction of CB in the cortex increases, the response range first increases and then decreases. The minimum value is 267.72%, and the maximum value is SCCB. 35 The fiber has a volume fraction of 595.59%. Using the same test method, the volume fraction of CB in the CB / TPU homogeneous conductive composite fiber of Example 2 increased from 12.0% to 16.0%, and the maximum response range increased from 71.60% to 101.34%, which was only increased by 41.54%. The maximum response range was 101.34%. It can be seen that the performance of the skin-core fiber in the response range has been greatly improved. This is also due to the fact that the post-coating preparation method can increase the volume fraction of the conductive filler, obtain a conductive network with a higher density of conductive fillers, and provide more conductive nodes and a wider response range.
[0058] Table 1. Maximum response range of different skin-core conductive composite fibers (mm / mm)
[0059]
[0060] (2) Sensitivity GF and linear range of skin-core fiber
[0061] The sensitivity of strain sensing fiber is the main parameter for evaluating its strain sensing performance, which is expressed as the ratio of the relative change in resistance (ΔR / R0) to the strain change value. For flexible conductive polymer composite fibers, their electrical signals are usually not linear during uniaxial stretching and show different sensitivities, but this nonlinear electromechanical response will complicate subsequent signal processing. Therefore, for conductive polymer composite fiber materials whose electromechanical response is not a linear relationship, we select the first linear region as the optimal use range of fiber sensing and calculate the GF value in this region.
[0062] The calculation formula of GF value is as follows:
[0063]
[0064] Among them, R0, ΔR, and ε represent the initial value of the resistance of the fiber sample before the loading experiment, the resistance change of the sample after elongation, and the strain size, respectively.
[0065] Fig. 9The graph of the electrical signals of different skin-core fibers with increasing strain within the deformation range of 80.0% shows that all skin-core fibers show good linear sensing capabilities within this range. 45 Taking the conductive composite fiber as an example, the GF value of the fiber in this range is calculated to be 2.72. A linear fitting is performed on this part of the electrical signal, and the fitting value is 0.997, indicating that the skin-core fiber can provide a high linear electrical signal response within the strain range of 80.0%.
[0066] The linear ranges of different core-skin fibers prepared in Example 1 and their GF values within the ranges are shown in Table 2. The first linear ranges of all core-skin fibers are greater than 100.0%, and the initial GF values are between 1 and 2. This shows that the preparation method of the present invention successfully reduces the influence of polymer viscoelasticity on signal linearity.
[0067] Table 2. Linear range of different sheath-core fibers and GF values within their range
[0068]
[0069] (3) Response speed
[0070] SCCB 45 Take the sheath-core fiber as an example to calculate the response time of the sheath-core fiber. The fiber is subjected to an 8% stretch response cycle. The time required for the fiber to stretch from the initial state to 8% strain is 0.016s, or 16ms. The time required for the resistance change to be divided by the stretching time is the response time of the conductive composite fiber. The obtained SBCB 45 The response time of the fiber is 449 ms, indicating that it has a high response speed.
[0071] (4) Fiber response to different strain ranges
[0072] Select SCCB 35 Fiber samples, Fig.10 The following is the response behavior diagram of the fiber under small strain (0.5%, 1.0%, 2.0%, 3.0%) and large strain (10%, 20%, 40%, 60%). It can be seen that the skin-core fiber shows good signal linearity, repeatability and stability in both small and large strain ranges. The signal baseline does not change significantly during multiple loading processes and there is no shoulder peak phenomenon. Especially in the strain range of 10-60%, the peak value of each cycle under the same strain is almost the same, showing the good practical application value of this fiber in this strain range.
[0073] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A method for preparing an electromechanical responsive sheath-core conductive composite fiber, characterized in that: The following steps are involved: S1. Dissolving polyurethane in N,N-dimethylformamide to form a spinning solution, using a wet spinning device to extrude the spinning solution into a water bath to form nascent fibers, and collecting the nascent fibers that have passed through the water bath on a hard collecting tube in a spiral shape, with no intersections between the fibers, and then drying and annealing to obtain pure TPU fibers collected on the hard collecting tube in a spiral shape; S2, adding Tris to deionized water and stirring to dissolve, measuring the real-time pH value of the solution, and adding hydrochloric acid dropwise to the solution until the pH value drops to 8.5 to obtain a Tris-HCl buffer; Dopamine hydrochloride is added to a mixed solution prepared by Tris-HCl buffer and anhydrous ethanol to dissolve, thereby obtaining a dopamine solution; pure TPU fiber is immersed in the dopamine solution along with a hard collecting tube, and the hard collecting tube is taken out after stirring for 12 to 24 hours under normal temperature, aerobic and light-proof conditions, and finally rinsed with deionized water and dried to perform surface modification on the pure TPU fiber to obtain a modified fiber; S3, adding hydrogenated styrene-butadiene block copolymer to cyclohexane and stirring until completely dissolved, then adding carbon black and stirring ultrasonically to obtain a uniformly dispersed CB / SEBS conductive solution; After the modified fiber is immersed in the CB / SEBS conductive solution along with the hard receiving tube for 0.5 to 2 hours, the fiber is taken out from the plastic tube and dried to obtain a sheath-core conductive composite fiber with a CB / SEBS layer as a conductive sheath and TPU fiber as a core.
2. The method for preparing the electromechanical responsive sheath-core conductive composite fiber according to claim 1, characterized in that: In step S1, polyurethane is dissolved in N,N-dimethylformamide at a concentration of 180-220 mg / mL to form a spinning solution.
3. The method for preparing the electromechanical responsive sheath-core conductive composite fiber according to claim 1, characterized in that: In step S1, the as-spun fibers are bundled in a spiral shape on a receiving tube and dried and annealed in a blast oven at 80-90°C.
4. The method for preparing the electromechanical responsive sheath-core conductive composite fiber according to claim 1, characterized in that: The average diameter of the pure TPU fiber obtained in step S1 is 130-150 μm, the average diameter of the modified fiber after surface modification in step S2 is 210-230 μm, and the diameter of the sheath-core conductive composite fiber obtained in step S3 is 245-260 μm.
5. The method for preparing the electromechanical responsive sheath-core conductive composite fiber according to claim 1, characterized in that: In step S2, the concentration of dopamine hydrochloride is 2 mg / mL, the concentration of Tris-HCl buffer is 0.01 mol / L, and Tris-HCl buffer and anhydrous ethanol are mixed at a volume ratio of 1:
1.
6. The method for preparing the electromechanical responsive sheath-core conductive composite fiber according to claim 1, characterized in that: In step S2, the volume fraction of carbon black in the CB / SEBS conductive solution is 25-45%.
7. The method for preparing the electromechanical responsive sheath-core conductive composite fiber according to claim 6, characterized in that: In step S2, multi-walled carbon nanotubes with a volume fraction of 1 to 15% are also added to the CB / SEBS conductive solution.
Citation Information
Patent Citations
Multifunctional fiber and preparation method and application thereof
CN115595682A
KR20220073085A